Political Opinion Formation as Epistemic Practice: The Hashtag Assemblage of #metwo - Sebastian Berg; Tim König; Ann-Kathrin Koster (Media and Communication, 2020)
The article contributes to the literature on the political use of hashtags. We argue that hashtag assemblages could be understood in the tradition of representing public opinion through datafication in the context of democratic politics. While traditional data-based epistemic practices like polls lead to the `passivation' of citizens, in the digital constellation this tendency is currently challenged. In media like Twitter, hashtags serve as a technical operator to order the discursive fabrication of diverse publicly articulated opinions that manifest in the assemblage of tweets, algorithms and criticisms. We conceptualize such a critical public as an epistemic sensorium for dislocations based on the expression of experienced social imbalances and its political amplification. On the level of opinion formation, this constitutes a process of democratization, allowing for the expression of diverse opinions and issues even under singular hashtags. Despite this diversity, we see a strong tendency of publicly relevant actors such as news outlets to represent digital forms of opinion expression as unified movements. We argue that this tendency can partly be explained by the affordances of networked media, relating the process of objectification to the network position of the observer. We make this argument empirically plausible by applying methods of network analysis and topic modelling to a dataset of 196,987 tweets sampled via the hashtag #metwo that emerged in the German Twittersphere in the summer of 2018 and united a discourse concerned with racism and identity. In light of this data, we not only demonstrate the hashtag assemblage's heterogeneity and potential for subaltern agency; we also make visible how hashtag assemblages as epistemic practices are inherently dynamic, distinguishing it from opinion polling through the limited observational capacities and active participation of the actors representing its claims within the hybrid media system.
Keywords: 300; #metwo; assemblages; big data; datafication; democracy; epistemic practices; hashtag; network analysis; topic modelling; Twitter analysis